ChemInform Abstract: High‐Pressure Synthesis of A‐Site Ordered Double Perovskite CaMnTi2O6 and Ferroelectricity Driven by Coupling of A‐Site Ordering and the Second‐Order Jahn—Teller Effect. Issue 28 (15th July 2014) - Aimi, Akihisa; Mori, Daisuke; Hiraki, Ko‐ichi; Takahashi, Toshihiro; Shan, Yue Jin; Shirako, Yuichi; Zhou, Jianshi; Inaguma, Yoshiyuki
Abstract Ferroelectric A‐site‐ordered double perovskite CaMnTi2O6 is prepared from equimolar mixtures of MnTiO3 and CaTiO3 in Au (for single crystals) and Pt capsules (for polycrystalline material) under high‐pressure (TRY cubic multianvil press, 1200‐1700 °C, 7 GPa, 0.5 h) followed by annealing (N2 atmosphere, 500 °C, 6 h).